THE FACTORS CAUSING ENGLISH SPEAKING ANXIETY ON NON-ENGLISH MAJOR ACADEMICS WHILE USING ENGLISH AS A MEDIUM OF INSTRUCTION - Yildiz, Mustafa (TEFLIN Journal, 2021)
This qualitative study aims to reveal the factors causing English speaking anxiety on non-English major academics while using English as a medium of instruction. Eight non-English major academics with the experience of teaching in English participated in the present research. Semi-structured one-on-one interviews and e-mail interviews, which are qualitative data collection techniques, were used as data collection tools. Manual coding of qualitative data that requires in-depth reading of the transcripts and assigning codes and themes was used to interpret the data. The results reveal the situations that provoke speaking anxiety among the non-English major academics. They can be grouped under five main themes: academics’ English proficiency, academics’ self-evaluation, learner behaviors, learner inadequacies, and cultural differences. These five main themes can also be confined to individual factors, learner factors, and cultural factors. It can therefore be assumed that the factors causing English speaking anxiety on non-English major academics have to be considered within multidimensional aspects rather than simply originating from academics themselves